A new velvet Gecko (Gekkonidae: Oedura) from south-east Queensland, Australia - Couper, Patrick J.; Keim, Lauren D.; Hoskin, Conrad J. (Zootaxa, 2007)
It has long been suggested that the populations of the Zigzag Velvet Gecko Oedura rhombifer in south-eastern Queensland represent a distinct species. Here, we provide morphological data supporting this assertion, and describe these populations as Oedura jacovae sp. nov. This species is predominately arboreal and is found in open eucalypt forests between the distributions of its two most similar congeners, O. rhombifer to the north and O. lesueurii to the south. It is morphologically distinguished from its congeners by dorsal pattern, characteristics of the 1 st and 2 nd supralabial scales, and the degree of webbing between the 3 rd and 4 th toes. Preliminary genetic data shows that Oedura jacovae sp. nov. is most closely related to O. rhombifer and O. lesueurii but is highly divergent from both. Further sampling is required to refine distributional knowledge of O. jacovae sp. nov. and to determine zones of contact between it and its closest congeners. Oedura jacovae sp. nov. is widespread in south-eastern Queensland but is likely to be threatened by the extensive clearing of lowland eucalyptus forest communities. Competition from rapidly expanding populations of the introduced Asian House Gecko Hemidactylus frenatus is also of concern. The examination of comparative material in this study allows us to highlight a number of populations of O. rhombifer that are morphologically interesting and in need of taxonomic investigation. Additionally, we confirm that the lectotypes of O. rhombifer and O. lesueurii are consistent with the currently accepted concepts of these two taxa.